EVERYDAY LIFE OF DAGESTAN GORYANKAS IN THE SECOND HALF OF THE 19TH – EARLY 20TH C. IN THE PRE-REVOLUTIONARY HISTORIOGRAPHY - Dalgat, El'mira Murtuzalievna (History, Archeology and Ethnography of the Caucasus, 2023)
The article considers everyday life of goryankas (women of mountains) of Dagestan in the second half of the 19th – early 20th centuries, seen through the eyes of the Russian authors, as well as representatives of local peoples. Some factual material in the studies of domestic, in particular Dagestan researchers, devoted to various Dagestan ethnic groups, which also describe the everyday life of women, is of interest. The main principles of historical science served as a methodological basis for the study: the principles objectivity, scientific nature, analysis of the works of Russian and local authors containing information about the everyday life of a Dagestan woman in the second half of the 19th – early 20th centuries. The interest in the topic under consideration sparked in the early 19th century, but intensified in its second half with the final annexation of Dagestan to the Russian Empire. In 1846, the newspaper Kavkaz started to be published, and in the 60s – the Collections of information about the Caucasian mountaineers. The 10 volumes of this publication contain the most important material on Dagestan by both Russian and local authors. The historical sources that formed the basis for writing the article are diaries, notes, articles in periodicals, monographs, etc. The article lists the topics on the everyday life of mountain women, most often touched upon by pre-revolutionary authors. These are housework, participation in fieldwork, chores, etc. The author analyzes the views of Russian and local authors on women’s everyday life, and identifies differences in their assessments of the situation of the mountain women of Dagestan. The author comes to the conclusion that women’s everyday life in different regions of Dagestan had its own peculiarities: it depended on the level of socio-economic development of the region, on the type of economic activity of the population, on the development of trade and economic relations, etc. This was reflected in the labor balance between men and women. Women were more engaged in the work in the mountains, and men – in the plains. The issue of women’s everyday life in Dagestan requires further research, taking into account regional features.